One piece : Volume 4-5-6 East blue - Oda, Eiichiro 1975-; Caselman, Lance; Amemiya, Naoko (San Francisco, California Viz Media, 2010)
As a child, Monkey D. Luffy dreamed of becoming King of the Pirates. But his life changed when he accidentally ate the Gum-Gum Fruit, an enchanted Devil Fruit that gave him the ability to stretch like rubber. Its only drawback? He'll never be able to swim again-- a serious handicap for an aspiring sea dog! Years later, Luffy sets off on his quest to find the "One Piece," said to be the greatest treasure in the world
vol. 4. Black Cat pirates -- vol. 5. For whom the bell tolls -- vol. 6. Oath.
Cover title.
This book reads from right to left.
Compilation of the graphic novel volumes 4-6 in the series.
Rated: T, for teen.
111566
Keywords: Pirates -- Comic books, strips, etc; Swordsmen -- Comic books, strips, etc; Treasure troves -- Comic books, strips, etc; Graphic novels -- Japan -- Translations into English; Pirates -- Fiction; Buried treasure -- Fiction; Cartoons and comics; Comics & Graphic novels -- Manga -- Fantasy; Comics & Graphic novels -- Manga -- Media Tie-In.; Japan; Anime; Young adult fiction; Graphic novels; Fictional Work; Fiction; Comics (Graphic works); Action and adventure fiction; Translations; Adventure fiction